LEARNING OPHTHALMOLOGY DURING THE COVID-19 PANDEMICS: IS REMOTE LEARNING APPLICABLE? - silva, jailton vieira; Neto, João Aurélio de Sousa; Vieira, Amanda Alexia Rodrigues; Vieira, Adah Sophia Rodrigues; Pereira, Guilherme Lopes; Ysla, Luiz Enrique D’Almeida Santos; Brasil, Thiago Praça (Health and Society, 2021)
Abstract: During the COVID-19 pandemic, there was a need to adopt a pedagogical approach that complies with distancing standards, without harming the student’s teaching-learning process. In this context, the search for tools that were effective for this period began, one of which was Remote Learning (RE). This paper seeks to report the experience of using RE as a teaching method for Ophthalmology. The experience was carried out with students from the Liga da Visão (LIVISA) at the Universidade de Fortaleza, through two stages: asynchronous virtual activities, aimed at the development of clinical skills, and synchronous theoretical classes, in partnership with academic residents, from an Ophthalmology service. Under this proposal, LIVISA’s mentor had the challenge of continuing the activities in the RE modality, following the methodology already applied at the University, problem-based learning (PBL). In view of this, the proposition of clinical cases was fundamental to instigate the student to acquire knowledge and stimulate clinical reasoning, based on ophthalmological situations, allowing a more active role for the student. The transposition of Ophthalmology teaching to LIVISA students, from face-to-face to remote, was essential to keep the group cohesive.